'As It Is Written' … Where? Examining Generic Citations of Scripture in the New Testament. (June 2021) - Lanier, Gregory R.
This article examines 33 'generic' citations of Israel's scriptures in the NT, defined as passages containing an introductory formula or other overt reference to a source, but lacking any actual quoted text. Each passage (from the gospels, Acts and Pauline epistles) is examined in terms of its citation form and particular meaning in context, and then this broader pattern of 'generic' citation is compared with Second Temple citation practices. Having rarely been studied collectively, these citations provide interesting insight into how the NT authors draw upon the whole of the OT – without reference to specific prooftexts – to make assertions about Israel's history, Christology, and the church. They should be given more consideration in the broader field of biblical intertextuality.